Influence of process variables on growth of ZnO nanowires by cathodic electrodeposition on zinc substrate - Sheini, Farid Jamali; Mulla, Imtiaz S.; Joag, Dilip S.; More, Mahendra A. (Thin Solid Films, 2009)
Influence of the deposition duration and electrolyte concentration on the structural and morphological features of the ZnO thin films, grown by cathodic electrodeposition on zinc substrate followed by annealing in air at 400 degrees C, have been investigated. The surface morphology of the as-synthesized films shows two distinct features, presence of `2-dimensional nanosheets' on the area near the electrolyte-air interface and `granular' nanostructures, below the interface region. However, upon annealing, the formation of ZnO nanowires, possessing length of several microns and diameter less than 20 nm, on the entire substrate is observed. The X-ray and selected area electron diffraction patterns clearly confirm the polycrystalline nature of the ZnO nanowires. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Annealing; Electrodeposition; Nanowires; photoluminescence; scanning electron microscopy; transmission electron microscopy; Zinc oxide